On Some Problems of Sex-Oriented Linguistic Behavior in Modern English: (A Sociolinguistic Approach) - Harutyunyan, Gohar; Mkrtchyan, Ashkhen (Armenian Folia Anglistika, 2011)
The article investigates the linguistic expressions of sex as a decisive social factor. An attempt is made to question the topicality of some of the characteristics of female speech elaborated by R. Lakoff which later turned into generally accepted beliefs.